Reports on the Prevalence of Clinical Conditions Are More Convincing When Supported by Objective Evidence - Schachter, Julius; Bailey, Robin; Dawson, Chandler R.; Lietman, Thomas M. (PLOS Neglected Tropical Diseases, 2008)
null